Teaching/learning in a e-school - Menezes, Helena (2003)
Education based on ODL and e-learning platforms are giving their first steps in Portugal. This paper gives a general overview of the main projects that tried to implement e-learning environments in Portugal and discusses the advantages and the problems that these platforms can raise. It is also referred a present application under Comenius 2.1 developing a curriculum for in-service teacher training.